Fact Sheet: West Nile virus - Yasmin Tavares; Amely Bauer; Lawrence Reeves; Lindsay Campbell (EDIS)
Introduced to the United States in 1999, West Nile virus (WNV) is transmitted from mosquitoes to humans and equines. With over 52,000 reported human infections, it is the most frequent cause of mosquito-borne disease in the continental United States. Many mosquito species can transmit WNV, and many wildlife species can be infected with the virus and transmit it to biting mosquitoes, which makes identifying WNV's high risk areas or time periods complex. The US equine industry, domestic pets, and livestock are all at risk from harm from WNV. Many equine WNV epizootics have occurred since 1999, with more than 30,000 equine cases reported in the United States. Since WNV's introduction to Florida in 2001, infections have been reported in a total of 460 people and 757 equines. This publication provides information about WNV to the general public, researchers and stakeholders in mosquito control, and public health professionals.